ANALISIS KESALAHAN BERBAHASA PEMBACA BERITA â€œKALBAR DALAM BERITAâ€ STASIUN TVRI KALIMANTAN BARAT - Febriana, Evva; Heryana, Nanang; Muzammil, Ahmad Rabiul (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Â AbstractThis research is motivated by the important of information submission by news listeners as a result of listening to the news. Researcher observed the error reading of news by the newsreader in â€œKalbar dalam Beritaâ€ program station TVRI West Kalimantan period February 2016. This study has a focus on the study of mistake differentiation, pronunciation, and intonation contained in the process of reading the news. The method used is descriptive research with the form of qualitative. The object of this research is newsreader in "Kalbar in Berita" program in stasius TVRI West Kalimantan in February 2016. Data collection is done by observing the video recording of news readings obtained from the administrative office of TVRI station West Kalimantan. Conclusion of this research is finding that happened some mistake cause by several things, such as too fast reading, uneasy condition, and inaccuracy in reading news. In total, there were 325 mistakes of differentiation, 509 mistakes of pronunciations, and 50 intonation mistakes made by some news readers, namely Asri Sabani, Yadi Saputro, Ida Robiatul Ula, Ari Munandar, Ayu Wulandari, Christina Novilia, Slamet Riki Haryadi, Mulyo Widodo, and Sri Maryanti. Mistakes in news reading are analyzed and corrected by researcher carefully and structured.Â Keywords: News Readers, Mistake Spoken, Kalbar Dalam Berita